DECISION SUPPORT SYSTEM FOR SELECTION OF SUPERIOR AND COMPETENT EMPLOYEES USING ANALYTICAL HIERARCHY PROCESS METHOD (AHP) AT UMKM DJOERAGAN AYAM PENYET IN EAST JAKARTA - Muhammad Reyhan Yafi; Yuliasari Yuliasari; Hadi Supratikta (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This study aims to implement a Decision Support System (SPK) using the Analytical Hierarchy Process Method (AHP) in selecting employees of Micro, Small and Medium Enterprises (MSMEs) Djoeragan Ayam Penyet East Jakarta. The AHP method is used to facilitate more objective and structured decision making in the employee selection process. This research involved interviews with MSME owners and related staff, direct observation in the employee selection process, as well as literature studies to gain an in-depth understanding of the concepts and applications of the AHP Method in the context of employee selection. The results show that the implementation of SPK using the AHP Method can improve objectivity, consistency, and efficiency in the employee selection process. Suggestions for the development and implementation of an effective SDM are also presented. This research contributes to the development of more scientific and measurable decision-making methods in human resource management, especially in the context of MSMEs.